Improving the Students’ Writing Skills by Integrating Problem-based Learning (PBL) with Teaching at the Right Level (TaRL) Approach in Class 7. C of SMP-TQ Mu’adz bin Jabal - A Tenry Lawangen Aspat Colle; Nurnia Nurnia; Rabiah Rabiah (Journal of English Language Learning, 2023)
This study aims to improve students' writing skills by integrating Problem-based Learning (PBL) with the Teaching at the Right Level (TaRL) approach in class 7. C of SMP-TQ Mu’adz bin Jabal. This study was collaborative Classroom Action Research (CAR), with a writing test, observation sheet, and e-questionnaire as research instruments. This study used three stages of statistical technique; first, measure the students’ writing skills using a writing scoring rubric. Second, determine the category of students' scores. Third, find out the class percentage of writing score category where it can be said the student's writing skills in 7. C improves if 70% of the total students obtained a very good category (81-100) as their learning objectives achievement criteria in their writing assessment. The study result revealed that the % of students' writing score category in cycle one is 48%, then increased in cycle two is 74%. It concluded that the writing skills in class 7. C improves. Further study is recommended to investigate the PBL in improving other language skills such as listening, speaking, and reading to establish more conclusive findings on its roles.